2x+1=6x+(-23)

Simple and best practice solution for 2x+1=6x+(-23) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+1=6x+(-23) equation:


Simplifying
2x + 1 = 6x + (-23)

Reorder the terms:
1 + 2x = 6x + (-23)
1 + 2x = 6x + -23

Reorder the terms:
1 + 2x = -23 + 6x

Solving
1 + 2x = -23 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
1 + 2x + -6x = -23 + 6x + -6x

Combine like terms: 2x + -6x = -4x
1 + -4x = -23 + 6x + -6x

Combine like terms: 6x + -6x = 0
1 + -4x = -23 + 0
1 + -4x = -23

Add '-1' to each side of the equation.
1 + -1 + -4x = -23 + -1

Combine like terms: 1 + -1 = 0
0 + -4x = -23 + -1
-4x = -23 + -1

Combine like terms: -23 + -1 = -24
-4x = -24

Divide each side by '-4'.
x = 6

Simplifying
x = 6

See similar equations:

| 3k=-51 | | 3n+4=7n+4 | | 2+25x=20x+15 | | 3.4x=2.7 | | 5t+6=-24-t | | 36x/-8x | | b/3--17=20 | | y=-0.02x^2+1.6x | | 9x+9=8x+5 | | -2x-8x= | | 3(x-5)=2x+30 | | 2.7x-0.05x+0.75x=3.4x | | v/3-3=1 | | 36x=-8x | | 25b^4-211b^2+3024=0 | | 3(n-2)=3(2n+4) | | -10+2j=-2 | | 6x(4+3)= | | X^72/8x^4 | | -5(x-1)=-10x+20 | | B^0/ba^5 | | (9)(10)-(3)(4)= | | 3w+6+4w= | | 5x+6y=67 | | 7x(1/3xN)-4=10 | | 6x-3=14x-19 | | 4(z-3)=5-3z | | (7(1/3y))-4=10 | | (M)(10)=n | | 5x-10(x-2)=x^2 | | 3ab^2-6b= | | 15x=7x-(11-4x) |

Equations solver categories